Maternal dietary quality during pregnancy and child appetitive traits at 5-years-old: Findings from the ROLO longitudinal birth cohort study. (1st December 2022) - Delahunt, Anna; Conway, Marie C.; Callaghan, Shauna L.; O'Brien, Eileen C.; Geraghty, Aisling A.; O'Reilly, Sharleen L.; McDonnell, Ciara M.; Mehegan, John; McAuliffe, Fionnuala M.
Abstract: Maternal diet during pregnancy is an important determinant of birth outcomes and offspring health. The relationship between maternal diet quality during pregnancy and the development of appetitive traits in early childhood has not been extensively researched. We examined associations of maternal diet quality during pregnancy with child appetitive traits at 5 years old. This is a secondary analysis of the ROLO longitudinal birth cohort study. We assessed maternal diet during pregnancy using 3-day food diaries and evaluated diet quality using the Alternative Healthy Eating Index, modified for pregnancy (AHEI-P). Children's appetitive traits at 5-years-old were assessed using the Child Eating Behaviour Questionnaire (CEBQ) (n = 306). Average AHEI-P score over trimesters was calculated and stratified into tertiles. Maternal and child characteristics were examined across AHEI-P tertiles. Multiple linear regression was conducted to explore associations between maternal AHEI-P scores in each trimester and child appetitive traits at 5-years-old. Women with low AHEI-P scores were younger at childbirth and had higher BMI. In adjusted linear regression maternal AHEI-P was negatively associated with child 'Desire to Drink' (Trimester 1: B = −0.014, 95% CI = −0.025, −0.002, p = 0.017; Trimester 2: B = −0.013, 95% CI = −0.025, −0.001, p = 0.035). Trimester 3 AHEI-P was not associated with any child appetitive traits. Maternal diet quality in pregnancy may provide an early opportunity to positively influence the development of offspring's appetitive traits.